Analysis of bipolar membranes for electrochemical CO2 capture from air and oceanwater - Bui, Justin C; Lucas, Éowyn; Lees, Eric W; Liu, Andrew K; Atwater, Harry A; Chengxiang Xiang; Bell, Alexis T; Weber, Adam Z (Energy & environmental science, 2023)
Carbon dioxide (CO2) must be removed from the atmosphere to mitigate the negative effects of climate change. However, the most scalable methods for removing CO2 from the air require heat from fossil-fuel combustion to produce pure CO2 and continuously regenerate the sorbent. Bipolar-membrane electrodialysis (BPM-ED) is a promising technology that uses renewable electricity to dissociate water into acid and base to regenerate bicarbonate-based CO2 capture solutions, such as those used in chemical loops of direct-air-capture (DAC) processes, and in direct-ocean capture (DOC) to promote atmospheric CO2 drawdown via decarbonization of the shallow ocean. In this study, we develop an experimentally validated 1D model for the electrochemical regeneration of CO2 from bicarbonate-based carbon capture solutions and seawater using BPM-ED. For DAC, our experimental and computational results demonstrate that pH swings induced by BPM water dissociation drive the formation of CO2 at the cation-exchange layer|catholyte interface with energy-intensities of less than 150 kJ mol−1. However, high rates of bubble formation increase energy intensity at current densities >100 mA cm−2. Correspondingly, accelerating water dissociation catalysis and enacting bubble removal could enable CO2 recovery at energy intensities <100 kJ mol−1 and current densities >100 mA cm−2. For DOC, mass transport limitations associated with low carbon concentrations in oceanwater suggest that DOC is best suited for clean production of acid and base usable in downstream processes. These results provide design principles for industrial-scale CO2 recovery using BPM-ED.